The power roots and drivers of infidelity in international business relationships - Leonidou, Leonidas C.; Aykol, Bilge; Spyropoulou, Stavroula; Christodoulides, Paul (My University, 2019)
We propose a conceptual model of the power roots and drivers of infidelity in exporter-importer (E-I) working relationships. Based on data collected from 262 Greek export manufacturers, we confirm that the exercise of coercive power in the E-I working relationship by the exporter has positive effects on distance, opportunism, and uncertainty, as opposed to the exercise of non-coercive power that exhibit negative effects. In turn, distance, opportunism, and uncertainty each contribute toward driving infidelity in the relationship by the importer. The relationship length and relationship status were also found to have a control effect on infidelity.
Keywords: Exporting; Exporter-importer relationships; Infidelity; Power; Distance; Opportunism; Uncertainty